Penjelasan dengan langkah-langkah:
= 2x - y + xy - 8
= 2(3) - (-2) + 3(-2) - 8
= (2.3) - (-2) + (3.(-2)) - 8
= 6 - (-2) + (-6) - 8
= 8 + (-6) - 8
= 2 - 8
= -6
= 2(-1) - (-4) + (-1(-4) - 8
= (2.(-1)) - (-4) + (-1.(-4)) - 8
= -2 - (-4) + 4 - 8
= 2 + 4 - 8
= 6 - 8
= -2
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Penjelasan dengan langkah-langkah:
= 2x - y + xy - 8
= 2(3) - (-2) + 3(-2) - 8
= (2.3) - (-2) + (3.(-2)) - 8
= 6 - (-2) + (-6) - 8
= 8 + (-6) - 8
= 2 - 8
= -6
= 2x - y + xy - 8
= 2(-1) - (-4) + (-1(-4) - 8
= (2.(-1)) - (-4) + (-1.(-4)) - 8
= -2 - (-4) + 4 - 8
= 2 + 4 - 8
= 6 - 8
= -2
https://brainly.co.id/tugas/53279117?utm_source=android&utm_medium=share&utm_campaign=question